Evaluation of substrate treatments for the prevention of damping off. - Solano-Bonilla, María (2012)
The effect of various treatments (Vitavax, Orthocide, solarization and control), was evaluated on portions of soil inoculated with Fusarium sp in the germination stage of Cedrela tonduzii (sweet cedar). This fungus is one of the causes of damping off in the early stages of many species, negatively affecting growth and development of them and sometimes leading to death of seeds. Treatment that presented the highest germination rate and plant growth was solarization, indicated that this treatment achieved to control and to kill the presence of inoculum, compared to the other treatments. The use of this technique could improve the performance and production of species susceptible to this disease, at the seedling stage during the nursery period.